2020
DOI: 10.1073/pnas.2016017118
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation-dependent localization of TmaR that controls activity of a major bacterial sugar regulator by polar sequestration

Abstract: The poles of Escherichia coli cells are emerging as hubs for major sensory systems, but the polar determinants that allocate their components to the pole are largely unknown. Here, we describe the discovery of a previously unannotated protein, TmaR, which localizes to the E. coli cell pole when phosphorylated on a tyrosine residue. TmaR is shown here to control the subcellular localization and activity of the general PTS protein Enzyme I (EI) by binding and polar sequestration of EI, thus regulating sugar upta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
(87 reference statements)
2
11
0
Order By: Relevance
“…2C). Notably, we have previously shown that the neighboring residue of E73, a tyrosine in position 72 (Y72), gets phosphorylated, a modification often associated with LLPS (19), and that this event is required for TmaR activity as EI regulator (13). Jointly, the current and previous results highlight the importance of the negative patch around positions 96-77 in TmaR, and suggest that both the phosphorylation and the charge it confers affect TmaR ability to undergo LLPS in vivo.…”
Section: Identification Of Residues and Motifs That Are Required For Tmar Condensates Formationsupporting
confidence: 64%
See 4 more Smart Citations
“…2C). Notably, we have previously shown that the neighboring residue of E73, a tyrosine in position 72 (Y72), gets phosphorylated, a modification often associated with LLPS (19), and that this event is required for TmaR activity as EI regulator (13). Jointly, the current and previous results highlight the importance of the negative patch around positions 96-77 in TmaR, and suggest that both the phosphorylation and the charge it confers affect TmaR ability to undergo LLPS in vivo.…”
Section: Identification Of Residues and Motifs That Are Required For Tmar Condensates Formationsupporting
confidence: 64%
“…Of note, accumulating evidence suggest that many stages of the RNA life cycle in eukaryotes occur within biomolecular condensates (27). Further research is required for defining the protein and RNA content of TmaR condensates and the interactions among its constituents that enable the control of important pathways, sugar metabolism on one hand, as previously shown by us (13), and motility and biofilm formation on the other hand, as shown here.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations